Astaxanthin Extract from Haematococcus pluvialis and Its Fractions of Astaxanthin Mono- and Diesters Obtained by CCC Show Differential Antioxidant and Cytoprotective Effects on Naïve-Mouse Spleen Cells - Jurčacková, Zuzana; Ciglanová, Denisa; Mudroňová, Dagmar; Tumová, Lenka; Bárcenas-Pérez, Daniela; Kopecký, Jiří; Koščová, Jana; Cheel, José; Hrčková, Gabriela (Antioxidants, 2023)
Carotenoids are the most abundant lipid-soluble phytochemicals and are used as dietary supplements to protect against diseases caused by oxidative stress. Astaxanthin, a xanthophyll carotenoid, is a very potent antioxidant with numerous beneficial effects on cellular functions and signaling pathways. In this study, using spleen cells from healthy Balb/c mice, we report the bio-functional effects of an astaxanthin-rich extract (EXT) prepared from the microalga Haematococcus pluvialis and its astaxanthin monoesters-rich fraction (ME) and astaxanthin diesters-rich fraction (DE) obtained by fractionation of EXT using countercurrent chromatography (CCC). After incubation under standard culture conditions (humidity, 37 °C, 5% CO2, atmospheric oxygen), the viability of untreated splenocytes, as determined by the trypan blue exclusion assay, the MTT assay, and the neutral red assay, decreases to approximately 75% after 24 h compared with naïve splenocytes. This effect correlated with the decrease in mitochondrial membrane potential and the transition of ~59% of cells to the early stage of apoptosis, as well as with the decreased ROS production, indicating that hyperoxia in cell-culture deteriorates cell functions. They are restored or stimulated by co-cultivation with EXT, ME, and DE up to 10 μg/mL in the order EXT > DE > ME, suggesting that esterification increases bioavailability to cells in vitro. ROS and H2O2 concentrations reflect mRNA transcriptional activity of Nrf2, superoxide dismutase 1 (SOD1), catalase, and glutathione peroxidase 1, as well as SOD-mediated ROS conversion, whereas they inversely correlate with iNOS-mediated NO production. The highest-tested concentration of EXT, ME, and DE (40 μg/mL) is detrimental to cells, probably because of the overwhelming scavenging activity of astaxanthin and its esters for the reactive oxygen/nitrogen species required for cellular functions and signal transduction at low physiological concentrations. In this study, we demonstrate that differential activities of ME and DE contribute to the final antioxidant and cytoprotective effects of astaxanthin extract, which is beneficial in preventing a wide range of ROS-induced adverse effects, with DE being more effective. In addition, the selection of physioxia-like conditions for pharmacological research is highlighted.